Orai1 and Stim1 regulate normal and hypertrophic growth in cardiomyocytes. - Völkers, Mirko; Salz, Mareen; Herzog, Nicole; Frank, Derk; Dolatabadi, Nima; Frey, Norbert; Gude, Natalie; Friedrich, Oliver; Koch, Walter J.; Katus, Hugo; Sussmann, Marc A.; Most, Patrick (Journal of molecular and cellular cardiology, 2010)
Cardiac hypertrophy is an independent risk for heart failure (HF) and sudden death. Deciphering signalling pathways dependent on extracellular calcium (Ca(2+)) influx that control normal and pathological cardiac growth may enable identification of novel therapeutic targets. The objective of the present study is to determine the role of the Ca(2+) release-activated Ca(2+) (CRAC) channel Orai1 and stromal interaction molecule 1 (Stim1) in postnatal cardiomyocyte store operated Ca(2+) entry (SOCE) and impact on normal and hypertrophic postnatal cardiomyocyte growth. Employing a combination of siRNA-mediated gene silencing, cultured neonatal rat ventricular cardiomyocytes together with indirect immunofluorescence, epifluorescent Ca(2+) imaging and site-specific protein phosphorylation and real-time mRNA expression analysis, we show for the first time that both Orai1 and Stim1 are present in cardiomyocytes and required for SOCE due to intracellular Ca(2+) store depletion by thapsigargin. Stim1-KD but not Orai1-KD significantly decreased diastolic Ca(2+) levels and caffeine-releasable Ca(2+) from the sarcoplasmic reticulum (SR). Conversely, Orai1-KD but not Stim1-KD significantly diminished basal NRCM cell size, anp and bnp mRNA levels and activity of the calcineurin (CnA) signalling pathway although diminishing both Orai1 and Stim1 proteins similarly attenuated calmodulin kinase II (CamKII) and ERK1/2 activity under basal conditions. Both Orai1- and Stim1-KD completely abrogated phenylephrine (PE) mediated hypertrophic NRCM growth and enhanced natriuretic factor expression by inhibiting G(q)-protein conveyed activation of the CamKII and ERK1/2 signalling pathway. Interestingly, only Orai1-KD but not Stim1-KD prevented Gq-mediated CaN-dependent prohypertrophic signalling. This study shows for the first time that both Orai1 and Stim1 have a key role in cardiomyocyte SOCE regulating both normal and hypertrophic postnatal cardiac growth in vitro.
Keywords: Stim1; Orai1; Hypertrophy; Cardiac; Calcium